'Violent exchanges : genre, national cinemas and the politics of popular films': case studies in Spanish horror and American martial arts cinema - Willis, Andrew (2007)
This thesis argues that in order to understand the way in which films work one has to place them into a variety of contexts. As well as those of production, these include the historical and culturally specific moments of their creation and consumption. In order to explore how these contexts impact upon the textual construction of individual and groups of films, and our potential understanding of them, this study offers two contrasting case studies of critically neglected areas: Spanish horror cinema since the late-1960s; and US martial arts films since the late 1980s.